Perlindungan HAM dalam konteks kekerasan gender perspektif pancasila - Maulana, A. Habil; Shofa, Muhammad Firdaus; Abdillah, Ilham Dharma (Maliki Interdisciplinary Journal, 2024)
Human rights are something that must be owned by every individual who is born as a human being. Human beings have human rights because they are human beings. Human rights are universal, cannot be limited and violated and apply to anyone, anywhere and anytime. The only thing that can limit human rights is the rights of others. As the basis of the Indonesian state, Pancasila contains values related to the continuity of human rights, starting from the implementation, prevention, to countermeasures when human rights are violated. The application of Pancasila values is expected to be able to help the community to understand, implement, and respect human rights, which as we know, Indonesian people are very unfamiliar with what human rights are. So we can see today with the rampant cases of human rights violations that occur including gender violence. By applying the values of Pancasila, Indonesian society can become a peaceful and harmonious society due to the fulfillment of their rights as human beings and the absence of human rights violations in Indonesia.